ANALISIS PENGARUH LIKUIDITAS, LEVERAGE, AKTIVITAS, PROFITABILITAS, DAN GROWTH TERHADAP KEBIJAKAN DIVIDEN EMITEN YANG TERDAFTAR PADA INDEKS LQ-45 PERIODE 2011-2013 - Sulaiman, Hengky; Sumani, Sumani (Jurnal Manajemen, 2016)
Dividend is component of return that investor gain on stock investment. On other side, dividend policy is major cash outlay for the company. The research goal is to reveal the factor that significantly influence the dividend policy, which can be used to maximize the investorâs return and provides guidance for the company in determining dividend policy. The research used sixteen company listed on LQ-45 Indexes during 2011-2013 by using panel data analysis. The research shows that activity and growth significantly affect the dividend policy while liquidity, leverage, and profitability insignificantly affect the dividend policy.Keywords: Dividend Payout Ratio, Likuiditas, Leverage, Aktivitas, Profitabilitas, Growth, Panel Data Analysis, Random Effect Model